2020
DOI: 10.3390/ijerph17239089
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Teachers on Motivation and Academic Stress and Their Effect on the Learning Strategies of University Students

Abstract: Students often experience the university period as a very stressful time. The teacher is a key figure who can cushion this stressful experience for the student. This study therefore aims to analyse the influence of teachers from the Self-Determination Theory perspective on academic stress, motivation, critical thinking, metacognitive strategies and academic performance in university students. The study involved 2456 university students with an average age of 22.51 years. A structural equation model was created… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 52 publications
1
23
0
5
Order By: Relevance
“…To our knowledge, this was the first study to investigate relations between these variables among Chinese students by using the serial mediation model. academic stress throughout their secondary school (41), high school (44), and university (45,46), educational careers. Studies have shown that academic stress has been positively associated with depression (41), PSQ (24,47), and MPA (48) among students.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this was the first study to investigate relations between these variables among Chinese students by using the serial mediation model. academic stress throughout their secondary school (41), high school (44), and university (45,46), educational careers. Studies have shown that academic stress has been positively associated with depression (41), PSQ (24,47), and MPA (48) among students.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the outcomes of the present study are congruent with some other studies in other subject fields; for example, Johnston-Wilder et al (2014) in their study indicated that learners with more degrees of resilience could manage the traumatic and demanding circumstances efficiently and they experience mathematical anxiety less. Correspondingly, research carried out by Trigueros et al (2020) with college learners indicated that learners with great levels of resilience were less anxious when dealing with a test. Resilience is maintained to eliminate the deconstructive impacts of worry and to improve an individual’s health.…”
Section: Discussionmentioning
confidence: 98%
“…The significance of resilience in educational settings is because the specific learners who encounter distressing and troubling circumstances become stronger without building any mental syndrome ( Robertson et al, 2017 ). Accordingly, resilience has been positively related to emotive intelligence, inner inspiration, and educational presentation ( Trigueros et al, 2020 ). Contrastingly, resilience has been negatively associated with apprehension, exam anxiety, and exhaustion ( Van Hoek et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Besides that, competition and participation in extracurricular activities make them more susceptible to developing mental health disorders such as anxiety and depression. 1 2 3…”
Section: Introductionmentioning
confidence: 99%